A new micropterous species of Haematoloecha from Vietnam (Hemiptera: Heteroptera: Reduviidae) - Santillan, Ian Gabriel C.; Rédei, Dávid (Zootaxa, 2025)
A new species of Haematoloecha Stål, 1874 (Hemiptera: Heteroptera: Reduviidae: Ectrichodiinae), H. merkli sp. nov., is described from northern Vietnam based on micropterous males and females. A checklist of species placed into Haematoloecha and currently considered valid is presented.